2016
DOI: 10.1111/gbb.12314
|View full text |Cite
|
Sign up to set email alerts
|

Functional conservation of MBD proteins: MeCP2 and Drosophila MBD proteins alter sleep

Abstract: Proteins containing a methyl-CpG-binding domain (MBD) bind 5mC and convert the methylation pattern information into appropriate functional cellular states. The correct readout of epigenetic marks is of particular importance in the nervous system where abnormal expression or compromised MBD protein function, can lead to disease and developmental disorders. Recent evidence indicates the genome of Drosophila melanogaster is methylated and two MBD proteins, dMBD2/3 and dMBD-R2, are present. Are Drosophila MBD prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 105 publications
0
22
0
Order By: Relevance
“…Thirteen studies were identified by this systematic search as summarized in Table 1. We categorized the studies into three groups according to the species of animal used for modeling RTT, which were one on cynomolgus monkey (Y. Chen et al., 2017), two on Drosophila (Gupta, Morgan, Bailey, & Certel, 2016; Hess‐Homeier, Fan, Gupta, Chiang, & Certel, 2014), and 10 using mice (D'Cruz et al., 2010; Fuchs et al., 2018; Johnston et al., 2014; Li et al., 2015; Lo Martire et al., 2017; Moretti, Bouwknecht, Teague, Paylor, & Zoghbi, 2005; Ren, Ding, Funk, & Greer, 2012; Robinson, Plano, Cobb, & Riedel, 2013; Tsuchiya et al., 2015; Wither et al., 2012).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirteen studies were identified by this systematic search as summarized in Table 1. We categorized the studies into three groups according to the species of animal used for modeling RTT, which were one on cynomolgus monkey (Y. Chen et al., 2017), two on Drosophila (Gupta, Morgan, Bailey, & Certel, 2016; Hess‐Homeier, Fan, Gupta, Chiang, & Certel, 2014), and 10 using mice (D'Cruz et al., 2010; Fuchs et al., 2018; Johnston et al., 2014; Li et al., 2015; Lo Martire et al., 2017; Moretti, Bouwknecht, Teague, Paylor, & Zoghbi, 2005; Ren, Ding, Funk, & Greer, 2012; Robinson, Plano, Cobb, & Riedel, 2013; Tsuchiya et al., 2015; Wither et al., 2012).…”
Section: Resultsmentioning
confidence: 99%
“…While, sample size was available in eight mouse studies ranging from 4 to 31. For the two studies in Drosophila, using only males, the sample size ranged between 21 to 50 (Gupta et al., 2016) and 30 (Hess‐Homeier et al., 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the methyl-CpG binding domain (MBD) retains considerable functional identity across species 39 . As MBD protein family members translate these epigenetic marks to appropriate functional states, we simply asked if MBD proteins in Drosophila contribute to setting the behavioral strategies associated with reproductive isolation as well as survival behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Neural development of D. melanogaster is very well characterized and shows great similarity to humans (SÁNCHEZ-SORIANO et al, 2007). This organism has been successfully used in the understanding of several human neurodevelopmental conditions, such as Fragile X syndrome REEVE et al, 2005;BASSELL;SASAKI, 2009;CALLAN et al, 2010)(MONYAK et al, 2016 and other autism-related conditions, including those with mutations in NRXN1, CNTNAP2, NLGN3 and CYFIP1 (SCHENCK et al, 2003;HAHN et al, 2013;GUPTA et al, 2016;PARK et al, 2016). These research reinforce the relevance of this model organism into the study of ASD and other neurodevelopmental disorders.…”
Section: Capítulomentioning
confidence: 99%